Developing Cellular & Molecular Biomarkers for Anti-Inflammatory Activities of Probiotic Bacteria in Fermented Foods - E. Ahmed Farid; M. Gouda Mostafa; C. Ahmed Nancy (International Journal of Nutrition, 2019)
We present below a mechanistic cellular and molecular approaches for the development of Anti-Inflammatory biomarkersof Probiotic Bacteria in Fermented Foods. Probiotics are live microorganisms that promote human health by counteracting the noxious toxic gut microflora in human intestine, by modulating of the tight junctions, and by increasing mucin production, enforcing intestinal epithelial cell barrier function, modifying microbial community within the gut intestinal disorders, and improving immune responses associated with chronic inflammation in experimental animal models, collectively enhancing human health. Cytokine secretion by intestinal epithelial cells and macrophages are regulated by probiotics through key signaling pathways such as nuclear factor-κB and mitogen-activated kinases, resulting in alleviation of several disorders such as allergies, diabetes, obesity, heart diseases and cancer. MicroRNAs are small non-coding RNA molecules involved in transcriptional and post-translational regulation of gene expression by inhibiting gene translation. Using in vitro and in vivo approaches in cell lines and mice models to study effects of probiotic conditional media and heat-killed bacterial strains with anti-inflammatory effect to elucidate the mechanisms by which probiotics affect signaling pathways, and by using global cytokine and microRNA gene expression analyses approaches to develop biomarkers for studying different pro- and anti-inflammatory activities, and using statistical approaches to analyse the data, we show that cytokines and miRNAs have an essential role in regulation of cancerous and inflammatory pathways. This mechanistic approach will result in developing specific disease biomarkers for the early diagnosis of certain pathogenic states, as well as evaluating the effect of different dietary components on developed biomarkers in health states that will promote and enhance human health. Comparing the concordance of the in vitro to the in vivo research findings will confirm the correspondence of both approaches to each other. Moreover, this study will have a major public health relevance in elucidating the role of miRNAs and their targets in inflammation, paving the way to diagnosing and treating of pathogenic human disease stages.
Keywords: Animal models